Shear effectiveness of shallow-angle bent-up bars for reinforced concrete beams - Teo, W. (Thomas Telford Services Ltd, 2014)
Recently there has been a renewed interest in reinforced concrete research to re-look into the shear effectiveness of shallow-angle bent-up bars. In the early years of reinforced concrete construction, considerable attention was directed to the use of this type of reinforcing system. Despite such popularity, however, there has been only limited research reported in this area. Two test series, with shear span to effective depth ratios of 2.86 and 4.00, respectively, were conducted in this study. The results obtained indicated that the performance of shallow-angle bent-up bars was superior in both strength and deformation characteristics, and they were able to achieve total steel saving of up to 18 compared to stirrup reinforcement. The shear effectiveness of bent-up bars depends greatly on the shear span to effective depth ratio, the angle of inclination and its position. It is recommended that current code provisions should revise the shear contribution of bent-up bars to minimum 75 and the optimum angle to be equal to 25Ì. Â© ICE Publishing: All rights reserved